'Until that magical day…no campus is safe': reflections on how transgender students experience gender and stigma on campus. Issue 2 (3rd March 2016) - Johnston, Matthew S.
Abstract: Based on interview data garnered from two transgender university students (transman and transwoman) and a reflexive narrative analysis, this research found that some transgender students experience overt forms of gender discrimination, violence, and stigma on campus spaces. Particularly troubling are the inadequate athletic facilities, social organizations, and counselling resources available to trans students. There is a need to have more readily available staff members educated on trans needs and human rights. That said, some narratives emphasize the activist and resilient roles some trans students undertake to make campuses a safer and more gender-inclusive space for trans and cisgender communities. Given the small sample size, the goal of this paper is to raise larger awareness toward the social issues present amongst transgender students, and emphasize the need for further research on gender diversity, marginalization, stigma, and best practices within campus spaces.